The Iron Wall Doctrine by Vladimir Ze’ev Jabotinsky and Benjamin Netanyahu’s Israeli Regime Stance towards Palestine: A Prolongation of the Zionist Revisionist Ideology - Zakariah, Muhamad Hasrul (Journal of Al-Tamaddun, 2024)
This study discusses the political thoughts of the Revisionist Zionists after the First World War, with a special focus on the Iron Wall Doctrine mooted by its eminent leader, Vladimir Ze’ev Jabotinsky, in 1923. Subsequently, this discourse will examine the extent to which the Iron Wall doctrine and Jabotinsky’s political idealism are embodied in the current Israeli government’s stance towards Palestine, led by Prime Minister Benjamin Netanyahu. Based on historical methodology analysis, the essay asserts that Netanyahu’s government is acting according to the Iron Wall Doctrine constructed by Ze’ev Jabotinsky, particularly in the recent Gaza genocide campaign. The most important historical sources analysed in the study are the writings of Jabotinsky himself - The Iron Wall and The Ethics of the Iron Wall, published in 1923. In the Iron Wall Doctrine, the revisionist Zionists believe that a Jewish majority state could be achieved and maintained in Palestine through the will of the Zionists and the repression of the indigenous population, in other words, the Palestinians. Currently, the political ideology of the Likud government and Netanyahu can be interpreted as the prolongation of the right-wing weltanschauung established by Jabotinsky in the 1920s. The finding of this study concluded that the Iron Wall Doctrine and radical political idealism propagated by Jabotinsky are adhered to and practised by the current Israeli government led by Benjamin Netanyahu in addressing the Palestine uprising.